(untitled) (Training and Practice : Journal of Educational Sciences, 2020)
Hungary has been offering public preschool education for nearly 200 years. Professional training for preschool teachers began with the opening of the first preschool in Hungary. Terez Brunszvik hired 11 young women, and she devoted great care to their training. (Koverne, 1996) In 2019 Hungary celebrated the 60th anniversary of third-level preschool teacher training. The first colleges to offer preschool teacher training and certification were founded in Kecskemet, Sopron, and Szarvas. According to the 1958 regulations [26,1,1], in addition to the regular program two colleges were assigned to offer training and certification for preschool teachers specialized in teaching children of ethnic minority. The college in Sopron offers German language training and the college in Szarvas offers Slavic, Southern Slavic, and Romanian language training. In my research, I focused on the development of the German ethnic minority preschool teacher training program in Sopron.